2020
DOI: 10.1111/ped.14267
|View full text |Cite
|
Sign up to set email alerts
|

Association between children's sleep patterns and problematic behaviors at age 5

Abstract: Background: Night-shift lifestyles affect children as well as adults, and are associated with sleep and behavioral problems among children. This study aimed to investigate associations among sleep patterns, individual/environmental factors, and problematic behaviors in children at age 5 years. Methods: Data for sleep patterns, individual / environmental factors, and problematic behaviors for 8,689 5-yearold children were collected from health-checkup records. Problematic behaviors investigated were anxious beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…One study among 2-to 6-year-old children has indicated that anxiety symptoms are associated with a higher score of dietary behavioural problems (45). Sleep disturbances (such as late bedtime and short sleep duration) affect problematic behaviours including anxious behaviour in 5-year-old children (47). A longitudinal study has shown that infant sleep disturbances at 2 and 24 months predict anxiety symptoms at 3 years, and a bidirectional association with anxiety symptoms preceding later sleep problems seems to exist (25).…”
Section: Discussionmentioning
confidence: 99%
“…One study among 2-to 6-year-old children has indicated that anxiety symptoms are associated with a higher score of dietary behavioural problems (45). Sleep disturbances (such as late bedtime and short sleep duration) affect problematic behaviours including anxious behaviour in 5-year-old children (47). A longitudinal study has shown that infant sleep disturbances at 2 and 24 months predict anxiety symptoms at 3 years, and a bidirectional association with anxiety symptoms preceding later sleep problems seems to exist (25).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the relationship between sleep duration and EBPs has become a hot topic. Previous cross-sectional studies from different countries have consistently shown that preschool children who had insufficient sleep were likely to have more EBPs, such as aggressive behavior [ 8 ], total difficulties and prosocial problems [ 9 ], anxious and developmental behavior [ 10 ]. A previous longitudinal study in Norway showed that short sleep duration was significantly associated with an increased risk of concurrent EBPs at 18 months, and short sleep duration at 18 months could predict the EBPs at 5 years old [ 11 ].…”
Section: Introductionmentioning
confidence: 99%